Performance of Intra-EU reforms in Central Africa: Empirical Verification - Ngouhouo, Ibrahim; Mougnol, Alice Kos A (Mediterranean Journal of Social Sciences, 2012)
This study investigates the impact of preferential reforms of the mid-1990 implemented in CEMAC zone on thedeterminants of intra-regional trade. Using a gravity equation, the study shows the influence of each variable under studiesduring the two sub-periods (before and after the reforms that is 1984 -1993 and 1994 – 2003) on the intra-regional trade. Using agravity equation, the study shows the influence of each variable under studies during the two sub-periods on the intra-regionaltrade. The results show that the populations (both home and away), cultural linkages and the proximities were directly related tointra-regional trade after the reforms than before. At the same time, the transactions and transport costs were negatively relatedto the intra-regional trade, mostly after the implementation of reforms.